Letter to the editor UC-II® Undenatured type II collagen: update to analytical methods. Issue 1 (16th July 2019) - Lugo, James P.
Abstract: Supplementation with UC-II® undenatured type II collagen has been shown to provide joint health benefits for both healthy adults and adults with knee osteoarthritis in controlled clinical trials. These trials used UC-II® materials with undenatured type II collagen characterized by an ELISA method that utilizes a monoclonal antibody specific for epitopes expressed by undenatured type II collagen protein only. In 2014, we modified the sample preparation part of the ELISA method in order to reduce the amount of time devoted to this procedure. We undertook these modifications in order to provide commercial manufacturers with a streamlined assay methodology better aligned with their product testing requirements. In doing so, it altered the percent of undenatured collagen now reported for UC-II® undenatured type II collagen. The intent of this letter is to clarify that the UC-II® materials used in the published clinical research cited herein, and the commercially available ingredient, remain identical and to describe the rationale for the change in the extraction method.